Strengthening the Profile of Pancasila Students Based on Local Wisdom Through the Making of Jumputan Batik Fabric in Elementary School - Anang Ma'ruf Anang; Ahmad Fathoni; Murfiah Dewi Wulandari; Yeny Prastiwi; Laili Etika Rahmawati (STAI Hubbulwathan Duri, 2023)
The independent curriculum was launched in the form of a learning design that provides opportunities for teachers to explore local wisdom content that is integrated into learning. The Pancasila student profile, with six dimensions, serves as a valuable resource for both educators and students in undertaking initiatives related to the creation of jumputan batik cloth. The objective of this research is to examine the extent to which the initiative enhances the profile of Pancasila students by using local wisdom in the production of jumputan batik fabric. The present study employed a descriptive qualitative methodology utilising a case study technique. Data collection techniques using interviews, observation and documentation. Informants for interviews in this study were the principal and 2 class teachers, and research locations at a private Islamic School in Surakarta. Data were analyzed by data reduction process, data presentation and conclusion drawing. The results of the study show that a project to strengthen the profile of Pancasila students based on local wisdom entitled making jumputan batik cloth can lead to: (1) dimensions of Faith, Fear of God Almighty, and noble characterreflected in the activity pray before the implementation of the project. (2) The Global Diversity Dimension which is reflected in the activities of each group Provide input and opinion on the results of the project, (3) cooperative dimensionreflected in joint activities in one project group, (4) creative dimension reflected in the creative activities of creating and producing original project works.